Cross-sectional analysis of blood leukocyte responsiveness to interleukin-10 and interleukin-6 across age and physical activity level - Islam Hashim; Boultbee Jordan; Jackson Garett S.; Mui Alice L.; Little Jonathan P. (Translational Exercise Biomedicine, 2024)
To determine how the anti-inflammatory actions of interleukin-10 (IL-10) and IL-6 differ across age and physical activity levels.